Comprehensive Analysis Reveals Two Distinct Evolution Patterns of Salmonella Flagellin Gene Clusters - Liu, Yue; Zhang, Dao-Feng; Zhou, Xiujuan; Xu, Li; Zhang, Lida; Shi, Xianming (Frontiers in Microbiology, 2017)
Abstract Salmonella is one of the primary causes of foodborne disease, especially Salmonella enterica subsp. enterica (I) which has caused ~99% of clinical salmonellosis cases for humans and domestic mammals. The flagella genes, fliC and fljB, which encode the Salmonella phase 1 and phase 2 antigens respectively, are considered as the Salmonella serotype determinant genes, and contribute to the virulence of Salmonella. However, the evolution of the two flagellin genes is still not well understood. In this study, the fliC and fljB gene clusters were analyzed among 205 Salmonella enterica subspecies I genomes. The dataset covered 87 different serovars of S. enterica subsp. enterica and included nine genomes (six serovars) of four other Salmonella subspecies. Based on a pan-genome definition and flanked gene linkages, the fliC and fljB gene clusters were identified in 207 (91 serovars) and 138 (61 serovars) genomes, respectively. A phylogenetic tree constructed based on SNPs (Single Nucleotide Polymorphisms) of core genes were used to reflect the essential evolutionary relationships among various serovars. Congruence analysis was performed among the core genome and each gene of fliC and fljB gene clusters, with only fliA and fliS showing congruence to Salmonella core genome. Congruence was also observed among fliB, fliC/fljB, and fliD genes, and their phylogeny revealed a division into two major groups, which strongly corresponded to monophasic and biphasic serovars. Besides, homologous recombination events referring fliB, fliC/fljB and fliD were found to have mainly occurred within each group. These results suggested two distinct evolutionary patterns of Salmonella flagellin gene clusters. Further insight on the evolutionary implication of the two patterns and a framework for phase variation mechanism are needed to be further processed.